2011
DOI: 10.1063/1.3606531
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent magnetic anisotropies in epitaxial Fe/CoO/MgO(001) system studied by the planar Hall effect

et al.

Abstract: Published by the AIP PublishingArticles you may be interested in Volume contribution of exchange-coupling-induced uniaxial anisotropy in Fe/CoO/MgO(001) system

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 19 publications
2
61
0
Order By: Relevance
“…Similar scenarios have been reported in collinear systems 8,42,43 . By using x-ray magnetic dichroism, it was shown that both the unidirectional reversal characteristic and higher-order anisotropies can be present without the observation of the loop shift 8,44 .…”
Section: Resultssupporting
confidence: 63%
“…Similar scenarios have been reported in collinear systems 8,42,43 . By using x-ray magnetic dichroism, it was shown that both the unidirectional reversal characteristic and higher-order anisotropies can be present without the observation of the loop shift 8,44 .…”
Section: Resultssupporting
confidence: 63%
“…AFM spins in a CoO film grown on a MgO(001) flat surface prefer an in-plane direction with a strong four-fold anisotropy and the easy axis (EA) along the CoO<110> direction [23]. Because of spin-flopping coupling [24,25], field cooling in a Fe/CoO/MgO(001) system can induce a strong uniaxial anisotropy in the Fe film with the EA along the CoO<110> direction, which is close to the direction of the cooling field (H FC ), and with CoO AFM spins aligned perpendicular to H FC [26].…”
Section: Introductionmentioning
confidence: 99%
“…For an H FC that points in a direction perpendicular to the steps, one in-plane SRT of Fe moments was found around the T N of the CoO film. However, for an H FC direction parallel to the steps, we found two temperature-driven SRTs, and three CoO-thickness-driven SRTs [13,26]. Finally, the sample was capped by a 3 nm MgO layer, which was used as a protective layer for MOKE measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Magneto-Optics has been also utilized to develop well-established technologies like MO recording [2], optical isolators [3,4], as well as novel applications within a wide range of different fields. Only the most recent ones alone cover topics from biosensing [5][6][7], magnetoplasmonics [8], nanomagnetism [9,10], ultrafast magnetization dynamics [11][12][13], magnetization reversal processes [14][15][16], to the anomalous behavior arising from the exchange bias effect [17][18][19][20], for instance.…”
Section: Introductionmentioning
confidence: 99%